METHODS OF TEACHING GYMNASTICS ACTIVITIES TO PRESCHOOL CHILDREN (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the process of teaching gymnastics exercises to the younger generation, the effective methods and pedagogical approaches used in training, as well as the importance of such activities in promoting a healthy lifestyle. The impact of sports gymnastics on children's physical development is also highlighted.